Evaluation of Indoor Thermal Comfort on Office Buildingin Ternate City - M Rahim; B Hamzah (Bandar Lampung University (UBL), 2017)
This study aims to evaluate the thermal comfort in office building by analyzing temperature, humidity, and wind speed conditions in the room. Research method is performed with the measurement of thermal condition using LSI-LASTEM Multi Logger, HOBO data logger, and HOBO data logger with external sensor. At the time of measurement, thermal condition perceived by employees is observed through the questionnaires of Thermal Sensation Vote (TSV) and Thermal Comfort Vote (TCV). The results show that the thermal condition in office building is uncomfortable level. Natural ventilation system is not effective because of orientation and dimension of ventilations are minimal or not suitable standard, therefore the usage of air conditioning is increased